2015
DOI: 10.1021/acs.jpcc.5b04312
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reactivity of Naphthalenecarboxylate-Protected Ruthenium Nanoparticles: Intraparticle Charge Delocalization Derived from Interfacial Decarboxylation

Abstract: Ruthenium nanoparticles were prepared by thermolytic reduction of RuCl 3 in 1,2-propanediol containing sodium 2-naphthalenecarboxylate. Transmission electron microscopic measurements showed that the average diameter of the resulting 2-naphthalenecarboxylate-protected ruthenium nanoparticles (RuCOONA) was 1.30 ± 0.27 nm. Interestingly, hydrothermal treatment of the nanoparticles at controlled temperatures led to decarboxylation at the metal−ligand interface, and the naphthalenyl moieties became directly bonded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Interfacial reactivity of other ligands has also been exploited for effective intraparticle charge delocalization. 28,29 This has been demonstrated by nanoparticle-catalyzed decarboxylation at the metal−ligand interface, leading to direct bonding of functional moieties onto the nanoparticle surface.…”
Section: ■ Intraparticle Charge Delocalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interfacial reactivity of other ligands has also been exploited for effective intraparticle charge delocalization. 28,29 This has been demonstrated by nanoparticle-catalyzed decarboxylation at the metal−ligand interface, leading to direct bonding of functional moieties onto the nanoparticle surface.…”
Section: ■ Intraparticle Charge Delocalizationmentioning
confidence: 99%
“…Recently a wide variety of metal–ligand bonds have been formed and used to functionalize metal nanoparticles, beyond the conventional metal–thiolate (M–S) linkages . This is primarily motivated by results from earlier studies of the adsorption of hydrocarbons on transition-metal surfaces. , The bonding interactions are generally believed to involve dπ–pπ interactions between the transition metals and the terminal carbon moieties. For instance, metal–carbon (M–C) covalent bonds can be readily formed by using aryl diazonium as the precursors which exhibit significantly reduced interfacial resistance, as compared to the M–S counterparts. Metal–carbene (MC) π bonds are formed by using diazo derivatives as the capping ligands, , and metal–acetylide (M–C)/–vinylidene (MCC−) bonds are produced by the self-assembly of acetylene derivatives onto transition-metal surfaces. ,,, More recently, it has been found that olefin derivatives may also be exploited as new capping ligands for nanoparticle surface functionalization, as a result of platinum-catalyzed dehydrogenation, such that the produced acetylene moieties self-assemble onto the nanoparticle surfaces. , Of these, the formation of conjugated metal–carbon interfacial bonds is found to endow the nanoparticles with unprecedented optical, electronic and electrochemical properties, due to effective intraparticle charge delocalization among the nanoparticle-bound functional moieties. ,,,, Importantly, this may be readily manipulated by the electronic properties of the metal cores which serve as part of the chemical bridge for intraparticle charge transfer. , In addition, when multiple functional moieties are incorporated onto the same nanoparticle surface, specific electronic interactions with selective molecules/ions may also be exploited as an effective variable in gating the intraparticle charge transfer, a platform that has the potential for chemical sensing of specific molecules/ions , and deliberate manipulation of the nanoparticle electrocatalytic activity in fuel cell electrochemistry. , ,…”
Section: Introductionmentioning
confidence: 99%
“…The successful incorporation of the eFc ligands onto the TiO 2 nanoparticle surface was confirmed by 1 H NMR and FTIR spectroscopic measurements. [12,23,24]. The fact that no sharp features were observed, along with the absence of alkynyl (≡CH) protons at 2.7 ppm, suggests that the nanoparticles were spectroscopically clean and free of monomeric eFc ligands [25].…”
Section: Resultsmentioning
confidence: 95%